Study on the Relationship of Root Morphology and Phosphorus Absorption Efficiency With Phosphorus Uptake Capacity in 235 Peanut (Arachis hypogaea L.) Germplasms - Zhu, Suqing; Luo, Lu; Zhang, Xiurong; Zhao, Meiyu; Wang, Xiaoqian; Zhang, Junjie; Wan, Qian; Li, Xianrong; Wan, Yongshan; Zhang, Kun; Liu, Fengzhen (Frontiers in Environmental Science, 2022)
Peanut (Arachis hypogaea L.) is a significant oil and protein crop. Its yields greatly depend on the availability of phosphorus (P). The root morphology and P absorb efficiency are important factors affecting the P uptake capacity, but their relationships in peanuts are rarely reported. Here, we reported the effect of root morphology and P absorb efficiency on P uptake capacity in peanut using 235 germplasms. In this work, we use P uptake rate per plant to reflect the P uptake capacity. The P uptake capacity was significantly increased after low P treatment, and showed great differences among germplasms. Germplasms with higher P absorb efficiency and well-development root system have higher P uptake capacity. Under both P conditions, P absorb efficiency play more important roles than root morphology on P uptake capacity, and the P uptake rate per unit root dry weight and P uptake rate per unit root surface area contributed the most. The root morphology contributes more to P uptake capacity under low P treatment than under sufficient P condition, and root surface area contributed the most. Forty-eight germplasms with high P uptake capacity were screed and they had three different uptake strategies under low P treatment. These findings indicated that low P stress induce root growth and improve P absorb efficiency of peanut to ensure the plant get enough P, and provide new insights into the relationship between P uptake capacity, P absorb efficiency, and root morphology, and furnish important evaluation indexes for high P-efficient germplasms selection.